Efeito de variáveis individuais e contextuais na qualidade de vida relacionada a saúde bucal em pré-escolares - Guedes, Renata Saraiva (2012)
Background: Studies have suggested that subjective measures of oral health can be influenced by both individual and contextual factors. However, studies assessing the interaction of individual and contextual determinants of subjective measures of oral health are scarce. Objective: This study assessed the effect of individual and contextual variables on the oral health-related quality of life in preschool children (COHRQoL). Methods: We followed a cross-sectional design, with a multistage random sample of 478 preschool aged 1-5 years old, representative of Santa Maria, a southern city in Brazil. Caregivers completed a questionnaire validated in COHRQoL (ECOHIS) and answered questions about the socioeconomic status and social capital. The dental examination provided information on the prevalence of dental caries, dental trauma and occlusion of preschoolers. Data were analyzed using multilevel linear regression model. Results: The mean ECOHIS was 1.8 (SD:3.9) and the functional domain of the session was the most affected children (mean = 0.5, SD =1.4). The multivariable multilevel model identified dental caries, dental trauma, anterior open bite, low socioeconomic status and low feature of social capital as individuals determinants of poor self-perception and quality of life. At a contextual level, children who lived in areas without community cultural centers were more likely to have impacts on the quality of life. Conclusion: The areas with unfavorable social conditions and poor socioeconomic status and poor dental status have a negative impact on COHRQoL.